The cytokeratin 17 expression in primary ovarian tumors has diagnostic but not prognostic significance - Dundr, Pavel; Bazalová, Barbora; Bártů, Michaela; Bosse, Tjalling; Drozenová, Jana; Fabian, Pavel; Fadare, Oluwole; Hausnerová, Jitka; Jakša, Radek; Laco, Jan; Lax, Sigurd F; Matěj, Radoslav; et al. (Virchows Archiv, 2022)
We assessed the value of cytokeratin 17 (CK17) expression for the differential diagnosis between primary ovarian mucinous tumors and metastases from the gastrointestinal tract (GIT) and the significance of CK17 expression in a broad spectrum of primary ovarian tumors with respect to their prognosis. The sample set consisted of 554 primary ovarian tumors and 255 GIT tumors. In the primary ovarian tumors, a higher CK17 expression (in > 10% of tumors cells) was present only in 0-11.4% of all tumors (including mucinous tumors, micropapillary serous borderline tumors, clear cell, endometrioid, and high-grade serous carcinomas). The only exception was low-grade serous carcinoma, where higher CK17 expression was present in 24% of cases. Concerning GIT tumors, the higher levels of CK 17 expression (in > 10% of tumor cells) were observed in the upper GIT tumors (68.5% of pancreatic ductal adenocarcinoma, 61.6% of gallbladder adenocarcinoma, and 46% of gastric adenocarcinoma), which differs substantially not only from most of the primary ovarian tumors, but also from colorectal carcinoma (3.7%; p < 0.001). The results of our study suggest that expression of CK17 can potentially be used as an adjunct marker in differential diagnosis between primary ovarian mucinous tumors and metastases from the upper GIT, but not from colorectal carcinoma. However, in GIT tumors, CK17 can be used in the differential diagnosis between adenocarcinomas of the upper and lower GIT. Statistical analysis did not reveal strong association of CK17 expression with clinicopathological variables or patient outcomes in any primary ovarian tumors.
Keywords: diferenciální diagnóza; kolorektální nádory; nádory vaječníků; Female; Gastrointestinal Neoplasms; ženské pohlaví; Colorectal Neoplasms; Pancreatic Neoplasms; keratin-17; Gastrointestinal tract tumors; Immunohistochemistry; Ovarian tumors; lidé; gastrointestinální nádory; nádory slinivky břišní; Ovarian Neoplasms; imunohistochemie; Diagnosis, Differential; Adenocarcinoma; Keratin-17; nádorové biomarkery; adenokarcinom; Cytokeratin 17; Biomarkers, Tumor; Differential diagnosis; Humans